Design of DC Electric Screw Jack Telescopic Push Rod Operated Scissor Lift - Ong, See Khin; Liew, Han Wei (INTI International University, 2022)
The scissor lift is widely used in industries as a lifting system to lift up load vertically. The scissor mechanism or pantograph with linked, folding supports in a criss-cross “X” pattern mostly powered by hydraulic system are used to achieve the upward motion. The power system employed on the scissor lift usually is a hydraulic system which installed at the lowest set of supports to elongate the crossing pattern and moving the platform on top of the scissor lift vertically. The primary components of the hydraulic system consist of reservoir, filters, pump, control valves, pressure relief valve and hydraulic cylinder. Hydraulic systems are more complex and expensive and subject to leakage. In this study the solid model and assembly of the part has been developed by the Autodesk Inventor software. The finite element analysis of the system will also be investigated with the same software i.e. stress, deflection, and safety factor values of system elements should be obtained. The formulation of the equation to determine the effective load of scissor lift and general equation of force required to lift up the load versus the angle of inclination of scissor’s link have been derived. A large thrust DC electric screw jack telescopic push rod or electric actuator which is high precision, longer service life, cheaper and easy to be installed will be selected to replace the hydraulic system. As a result of the analyses, a prototype is fabricated with the system designed that should safely be used during loading and unloading operations.